Effects of Soy-Milk on Blood Lipids and Total Homocysteine Level in Postmenopausal Women of Bangladesh - Farjana Rahman Bhuiyan; Farzana Saleh; Israt Ara Hossain; Khursheed Jahan; Liaquat Ali (International Journal of Nutrition, 2017)
Background: Isoflavones are phytoestrogens present in natural sources, and they resemble estradiol in structure and manner of action. The aim of the study was to assess the effects of soy-milk on serum tHcy levels and to assess the glycemic and lipidemic status of Bangladeshi postmenopausal women. Methods: Thirty-six women (aged 50 ±5.16 years, M ±SD) participated in a randomized, un-blinded, open-ended, crossover study design for 52 days. The soy-milk group consumed 350 mL of milk twice a day for 21- day; the milk contained 30 mg of isoflavones. FBG, PPG, HbA1c, TC, TG, HDL-C, NEFA, and tHcy were measured on day 0, day 21, day 31, and day 52 with a 10- day washout period. Results: After the consumption of soy-milk, the level of HDL-C significantly (p=0.005) increased on day 21 in the subjects. No significant changes were observed between the groups. After crossover, significant changes in FBG (p=0.005) and TG (p=0.049) were observed on day 52 in the soy-milk group. Significant improvement in TG (p=0.001) and HDL-C (p=0.032) was also seen at the end-point. Conclusions: Soy isoflavones is to some extent favorable to reduce CVD risk factors among Bangladeshi postmenopausal women.
Keywords: Soy-milk